(untitled) (Global Journal of Human-Social Science, 2013)
The purpose of this study is to compare global knowledge and abilities between pre-service teachers and in-service teachers in Taiwan To collect data a questionnaire containing 40 items within four categories was developed and distributed to 537 samples The results indicated that pre-service teachers had more global knowledge than did in-service teachers in global correlation systems and global issues Moreover major and teaching fields had significant differences in global knowledge and abilities The results of this study can be applied to improve teacher education programs for global education and to increase global concerns for teachers in different fields